The Treacherous Imagination : Intimacy, Ethics, and Autobiographical Fiction - McGill, Robert, 1976- (Book collections on Project MUSE., 2013)
Many writers have been accused of betraying their loved ones by turning them into fictional characters. In this book, the author examines the ethics of writing such stories. He argues that while fiction has long appealed to readers with its narratives of private life, contemporary autobiographical fiction channels a widespread ambivalence about the value of telling all in a confessional age - an age in which fiction has an unprecedented power to leave people feeling libeled or exposed when they recognize themselves in it. Observing that the interests of authors and their loved ones in such cases are often less divergent than they appear, the author assesses strategies by which both parties might use fiction not to hurt each other but to revise and revitalize intimacy. Discussing authors such as Philip Roth, Alice Munro, A. S. Byatt, and Hanif Kureishi, the author questions whether people should always require exclusivity of each other with regard to the stories they tell about private life. Instead, authors and their intimates might jointly embrace fiction’s playful, transgressive qualities, even while reexamining the significance of that fiction’s intimations.